Inhibition of Sodium/Hydrogen Exchanger‐1 in the Right Ventricle and Lung Dysfunction Induced by Experimental Pulmonary Arterial Hypertension in Rats - Giuseppina Milano; Melanie Reinero; Julien Puyal; Piergiorgio Tozzi; Michele Samaja; Florence Porte‐Thomé; Maurice Beghetti (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Life‐threatening pulmonary arterial hypertension (PAH) still lacks a direct therapeutic approach targeted to the molecular defects associated with the disease. Here, we focus on the impaired regulation of intracellular acidity and sodium/calcium overload by testing the hypothesis that inhibiting NHE‐1 (sodium/hydrogen exchanger isoform 1) with rimeporide enables the recovery of pulmonary and right ventricular dysfunctions in the Sugen5416/hypoxia PAH model in rats. Methods and Results Adult Sprague–Dawley male rats (n=44) rats were divided into 2 broad groups: control and Sugen5416/hypoxia. After verifying PAH insurgence in the Sugen5416/hypoxia group by transthoracic echocardiography and pulse‐wave Doppler analysis, rats were treated with either 100 mg/kg per day rimeporide or placebo in drinking water for 3 weeks. The functional, morphological (fibrosis and hypertrophy), and biochemical (inflammation, signaling pathways) dysfunctions caused by PAH were partially reverted by rimeporide in both the lungs and myocardium, where the most striking effects were observed in the right ventricle. Rimeporide improved hemodynamics in the pulmonary circulation and in the right ventricle, with decrease in right ventricle hypertrophy, pulmonary vascular remodeling, inflammation, and fibrosis. No effect of rimeporide was detected in control rats. The protective effect of rimeporide was accompanied by decreased p‐Akt/Akt (phosphorylated protein kinase B/protein kinase B) ratio and increased autophagy flux mainly in the right ventricle. Conclusions By specifically inhibiting NHE‐1, rimeporide at the selected dosage revealed remarkable anti‐PAH effects by preventing the functional, morphological, and biochemical deleterious effects of PAH on the right ventricle and lungs. Rimeporide should be considered as a potential treatment for PAH.